Enzymatic Biotechnology in Modifying the Functional Properties of Plant Proteins - Hartono, Adi (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2025)
Enzymatic biotechnology offers an innovative and environmentally friendly approach to modifying the functional properties of plant proteins to support the development of value-added foods. The urgency of this research lies in the increasing need for alternative protein sources that are not only highly nutritious but also have functional characteristics suitable for the formulation of modern food products and those intolerant to animal protein. This study aims to systematically examine the role of various enzymes, such as proteases, transglutaminases, and oxidoreductases, in improving the solubility, water and oil binding capacity, gel formation, and emulsification properties of plant proteins from soybeans, nuts, wheat, and microalgae. This research method uses a systematic literature review approach to scientific publications published in the last five years obtained through the indexed databases Scopus and ScienceDirect. The results of the study indicate that enzymatic modification can significantly improve the functional performance of plant proteins without damaging the structure of essential amino acids, and opens up opportunities for broad applications in plant-based milk products, imitation meat, and functional beverages. The conclusions of this study confirm that enzymatic technology is a promising sustainable biotechnology strategy for improving the quality and competitiveness of plant proteins in the global food industry. The implication is that cross-disciplinary research collaboration between food biochemistry and process technology is needed to optimize the formulation and efficiency of plant-based food production. Keywords: Enzymatic Biotechnology; Modification; Functional Properties of Plant Proteins